Early Detection of Pregnancy Complications in Siabu Health Center, Mandailing Natal Regency - Lubis , Ayu Ulfah Nur; Sri Rezeki; Seri Wahyuni Harahap (PT Inovasi Pratama Internasional, 2023)
The world health agency or WHO issued a statement that the deaths that occur in mothers in the world are on average due to complications during pregnancy and also the delivery process. And in 2017 alone there were around 810 cases. Even though from the beginning of 2000 until now there has been a decrease in cases of up to around 38%, the mortality rate of pregnant women continues to be a concern of the World Health Organization. The statement also stated that the deaths received by these pregnant women globally occur in countries that have low GDP and middle income. Indonesia is one of the countries with a high rate of maternal mortality due to complications of pregnancy and childbirth. Assistance during labor and also during pregnancy must be a concern for medical personnel and also health workers. It is hoped that these medical personnel can provide skills and are also trained in treating pregnant women. Complete health facilities can be one way to reduce maternal and child mortality. Pregnant women must also have education, awareness and information about the importance of prenatal checks for medical personnel. Service on the community side of course has the aim of increasing the knowledge of pregnant women about anemia and early detection of complications in pregnancy. Education and information regarding early detection of pregnancy complications is the main concern of the Siabu Health Center, Mandailing Natal Regency.